45. Diabetic distal sensorimotor and autonomic polyneuropathy in adults with type 1 and 2 diabetes. Issue 4 (April 2016) - Ministeri, C.M.; Maccora, S.; Modica, A.A.; Aliquò, M.S.; Giordano, S.; Cardella, F.; Roppolo, R.; Maccora, I.
Abstract : Emerging evidence suggests that distal symmetric sensorimotor polyneuropathy (DSPN) and diabetic autonomic neuropathy (DAN) stems from nerve dysfunction in early stage of diabetes. Neurophysiological assessment can provide an early diagnosis of such complications and should be carried out at the diagnosis and during progression of the disease. We studied 44 patients, 24 type 2 diabetes (mean age 61 years, duration 14 years, mean HBA1 C 8, 2%) and 20 type 1 (mean age 19 years, duration 11 years, mean HBA1 C 8, 4%). All subjects complained of symptoms proper to peripheral neuropathy. Neurophysiological evaluation included Nerve Conduction Studies/Electromiography, Heart Rate Variability including time domains (mean RR-interval and RR-standard deviation), Sympathetic Skin Response (SSR). Peripheral neuropathies due to any other cause were excluded. The prevalence of DSPN, DAN and the association between DSPN and DAN was significantly higher in patients with type 2 compared with those with type 1 diabetes ( P  < 0.001), being the duration of disease and age significantly higher ( P  = 0, 01) in type 2 diabetes patients. Poor glycemic control and the disease duration are some of the concurrent factors in diabetic polyneuropathy and CAN pathogenesis. Since DSPN and DAN probably share the same pathogenesis, neurophysiological follow-up should be considered as a useful tool for early diagnosis of such complications. In our opinion, however, mean duration of diabetes and the age could be an important etiologic factor of PNS.